Rhys Matters
XVII, 271 p.
Keywords: Rhys Matters, the first collection of essays focusing on Rhys's writing in over twenty years, encounters her oeuvre from multiple disciplinary perspectives and appreciates the interventions in modernism, postcolonial studies, Caribbean studies, and women's and gender studies.